Footing Under Static Loading: Land Subsidence - Budihardjo, Mochamad Arief; Yang, S.; Chegenizadeh, Amin; Nikraz, Hamid (Science Publications, 2015)
Land and footing subsidence caused by groundwater extraction is a source of many problems for buildings and infrastructures. This study aims at extending the knowledge of footing subsidence causing by ground water pumping by considering various well and load conditions. The approach is to use PLAXIS simulation to investigate the influence of well conditions on the subsidence of surface footing subjected to combined distributed load. A number of soil models with plain strain, homogeneous and transient flow behavior were built. While the groundwater extraction rate was set up at 20 m3/day for each well, the obvious influence of important parameters including well numbers, well location and load magnitude on footing subsidence and surface profile were investigated. It was found that increasing the number of wells will trigger greater footing subsidence, while the location of the wells will slightly affect the surface profile of both the aquifer and footing. In this study, the effect of distributed load above the footing to the footing itself was also investigated by doubling the distributed load applied. The simulation results showed that distributed load significantly contribute to the subsidence of footing.